STUDI DESKRIPTIF MANFAAT PEMBELAJARAN MATA KULIAH ELEKTIF COFFEE BUSINESS AND MANAGEMENT - Wijanarti, Sri Widya; Kusmulyono, Muhammad Setiawan (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2018)
The trend of coffee business has increased sharply in the last three years and has become a prospective business opportunity. One response to this trend is making courses on coffee business and management. This qualitative research method aims to evaluate the learning benefits of Coffee Business and Management elective courses in the Prasetiya Mulya University, S1 Business Program, in 2017-2018 academic year. The results of the study revealed that the majority of students who took this course argued that they have interests to know the coffee business and industry in Indonesia. The most interesting material in this course is dominated by practical learning about coffee in the laboratory. The most important result, 90% more students from Coffee Business and Management courses are inspired to run a coffee business.